(untitled) (Altre Modernità, 2020)
The reworking of new identities as a result of migratory movements is largely defined by the multilingual nature of the subjects. The adoption of the language of the host country, as an indispensable requirement for integration, together with the maintenance to a greater or lesser extent of the language of the country of origin characterizes the sociolinguistic profile of first and second generation migrants. This is a paradigmatic social phenomenon of continuity and disruption of the cultural background of individuals in contemporary societies. The present study addresses the role of language in shaping the identity of young people in a specific migration context: the Hispanic American population in Italy. In particular, will be analyzed the case of Spanish-speaking university students as representatives of an intermediate generation fully integrated in Italian society and that, at the same time, maintains a strong link with their cultural roots.